Evaluasi Daya Gabung dan Heterosis Lima Galur Jagung Manis (Zea mays var. saccharata) Hasil Persilangan Dialel - R. Neni Iriany (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2011)
The objective of this research was to estimate general combining ability (GCA), specifi c combining ability (SCA),and heterosis of fi ve sweet corn inbreds in order to be selected to develop hybrid varieties. Five inbred lines as parent wereMr12/SC/BC4-6-1B-1, Mr14/SC/BC4-6-1B-1, Mr4/SC/BC4-2-1B-1, Mr11/SC/BC4-2-1B-1, and Mr12/SC/BC3-3-1B-1. Theexperiment was conducted from April to June 2010 using a Randomized Complete Block Design with two replications atIndonesian Cereal Research Institute (ICERI) experimental station, Maros, South Sulawesi. Analyses of GCA and SCA werebased on the Griffi ng’s fixed model of Diallel Design Method I. Heterosis values were predicted based on the average valuesof their parents whereas heterobeltiosis were predicted based on the average values of the highest parents. Cross B x D(Mr14/SC/BC4-6-1B-1 x Mr11/SC/BC4-2-1B-1) had the highest SCA for yield 990.67. Cross A x B (Mr12/SC/BC4-6-1B-1 xMr14/SC/BC4-6-1B-1) had the highest SCA for ear diameter 0.36. Cross A x D (Mr12/SC/BC4-6-1B-1 x Mr11/SC/BC4-2-1B-1) had the highest heterosis and heterobeltiosis for yield, while Cross A x D (Mr12/SC/BC4-6-1B-1 x Mr11/SC/BC4-2-1B-1)had the highest heterosis and heterobeltiosis for ear length. Cross A x B (Mr12/SC/BC4-6-1B-1 x Mr14/SC/BC4-6-1B-1) andE x A (Mr12/SC/BC3-3-1B-1 xMr12/SC/BC4-6-1B-1) had the highest heterosis and heterobeltiosis for ear diameter.Keywords: combining ability, diallel crossing, heterosis, sweet corn